Hypofractionated whole breast irradiation with simultaneous integrated boost in breast cancer using helical tomotherapy with or without regional nodal irradiation: A report of acute toxicities - Chitapanarux, Imjai; Nobnop, Wannapha; Onchan, Wimrak; Klunklin, Pitchayaponne; Nanna, Thongtra; Sitathanee, Chomporn; Kulpisitthicharoen, Sutthisak; Sripan, Patumrat (Frontiers in Oncology, 2023)
Purpose: We prospectively investigated the acute toxicities focusing on skin and hematologic function in breast cancer patients who received hypofractionated whole breast irradiation with simultaneous integrated boost (HF-WBI-SIB) with helical tomotherapy (HT), with or without regional nodal irradiation (RNI). Methods: The dose of WBI and RNI was 42.4 Gy in 16 fractions. Tumor bed was prescribed to 49.6 Gy in 16 fractions simultaneously. The association between the worst grade of acute toxicities during treatment and receiving RNI was analyzed. The integral dose to the whole body between the two groups was also compared. Results: Between May 2021 and May 2022, 85 patients were enrolled; 61 patients received HF-WBI-SIB only (71.8%) and 24 patients (28.2%) received HF-WBI-SIB with RNI. Grade 2 acute skin toxicity was found in 1.2%. The most frequent grade 2 or more hematologic toxicity was leukopenia, which occurred in 4.8% and 11% in the 2nd and 3rd week, respectively. Mean whole body integral dose was significantly higher in patients treated with RNI compared to patients treated without RNI: 162.8 ± 32.8 vs. 120.3 ± 34.7 Gy-L (p-value < 0.001). There was no statistically significant difference in acute grade 2 or more skin and hematologic toxicities between the two groups. Conclusions: HF-WBI-SIB with or without RNI is feasible with acceptable acute skin and hematologic toxicities. RNI and whole body integral dose were not associated with these acute toxicities.